Development of an active suspension system for a Mercedes-Benz coach (O404) - Becker, M.; Jaker, K.-P.; Fruhauf, F.; Rutz, R. (1996 IEEE International Symposium on Computer-Aided Control System Design, 1996)
Coach active suspension system design must meet requirements for comfort and safety, and technical requirements. A hydropneumatic system was taken to be the most appropriate spring system. In a hydropneumatic strut, spring and damper elements are replaced by hydraulic ones, the flat spiral spring being replaced by a hydraulic accumulator and an actuator with the damper being replaced by a throttle and an actuator. The stabilizer is abolished altogether. After the statical properties were established a dynamical model of the entire coach, including active components, was made up helping to verify further dynamical loads and demands relating to control engineering. The article describes the design process.